Analytic Hierarchy Process : The Improvement of the Student Representative Committee Selection Method at Universiti Kuala Lumpur - Saaludin, Nurashikin; Saaludin, Nurashikin; Ismail , Mohd Hafizul; Abidin, Ira Syazwani Zainal; Mat, Basyirah Che (International Journal of Psychosocial Rehabilitation, 2020)
Higher learning institutions play a vital role in producing high-quality students with various aspects of skills and knowledge. The exposure of the leadership attributes through the involvement in the Student Representative Committee (SRC) is good for preparing students to face the challenges in the future. Student leaders are responsible to voice-out the peers’ views, ideas and issues which affect students’ lives including academic, welfare and co-curricular activities. Thus, choosing the right candidates for SRC is also crucial as they symbolise good universities’ governance. This study wishes to improve the method of SRC selection at Universiti Kuala Lumpur. The gathering of peers’ perception towards SRC through the focus group discussion highlighted several important leadership criteria; namely communication, organised, passionate, creative, commitment, teamwork and visionary. The Analytic Hierarchy Process (AHP) is used to prioritise the criteria which indicated that commitment, passionate and organised as the most dominant criteria. The submission of students’ curriculum vitae (CV), manifesto plan and the application form are proposed as an additional requirement in filtering the SRC application. The process is important to ensure that the selected SRC is truly qualified and able to fulfil the peers’ expectation, which will reflect the representation of the university.